CH–π interaction in VQIVYK sequence elucidated by NMR spectroscopy is essential for PHF formation of tau. Issue 3 (May 2014) - Sogawa, Koushirou; Minoura, Katsuhiko; In, Yasuko; Ishida, Toshimasa; Taniguchi, Taizo; Tomoo, Koji
ABSTRACT One of the histopathological features of Alzheimer's disease (AD) is higher order neurofibrillary tangles formed by abnormally aggregated tau protein. Investigation of the mechanism of tau aggregation is important for the clarifying the cause of AD and the development of therapeutic drugs. The microtubule‐binding domain, which consists of repeats of similar amino acids (R1–R4) is thought to form the core component of paired helical filament (PHF). The hexapeptide306VQIVYK311 of R3 has been shown to take a key role of promoting tau aggregation and assumed that its CH–π interaction between the side chains of Ile308 and Tyr310 would contribute in stabilizing the filament. In this work, we investigated a short isoform of tau (4RTau), R3, VQIVYK peptide and their mutants by thioflavin S (ThS) fluorescence, and NMR measurements, and proved for the first time that this CH–π interaction stabilizes the filament at the atomic level. In addition, by molecular modeling, we revealed that this interaction further supports an extended amphipathic structure for molecular self‐association during the process of PHF formation of tau protein. The present work indicates new approach that inhibits the CH–π interaction for developing a therapeutic agent for AD. © 2014 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 102: 288–295, 2014.